Polygamy in the family and marital sphere of the modern Dagestan society - Elvira Makhachevna Zagirova (Вестник Майкопского государственного технологического университета)
Polygamy as a form of family and marital relations, corresponding to Muslim ethics, not only becomes widespread in Dagestan society, but also causes conflicting assessments in the mass consciousness of the inhabitants of the Republic. These assessments have a pronounced gender connotation. In the mass consciousness of the female part of the Dagestan society, this phenomenon is more identified as a negative phenomenon, in contrast to that of the male part of the population. In this regard, the article aims to identify the factors that give rise to polygamous strategies in the family and marital behavior of Dagestan men, as well as various evaluative positions of such marital behavior on the part of the Dagestan population. In this perspective, the practice of polygamy in Dagestan has not yet been the subject of scientific analysis, which determines the innovative nature of the results obtained in the course of the author's empirical study. Based on the results of the author's sociological survey conducted in 2021, a key conclusion was made that a man's right to polygamous marital behavior, actualized in the context of the religious (Muslim) revival in the Dagestan society, diverges from traditional ideas about the family and marital relations among Dagestan women. They, for the most part, regardless of the degree of religiosity, show a negative attitude towards the practice of polygamy. The reason for such an imbalance in attitudes towards polygamy in Dagestan is the nature of this revived family and marital practice, inadequate to modern realities, which has lost its functional content, motivational grounds and behavioral ethics.